2013
DOI: 10.1542/peds.2012-3256
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Cytophagic Histiocytic Panniculitis in Children May Be Cured by Cyclosporine A

Abstract: Cytophagic histiocytic panniculitis (CHP) is a rare panniculitis in childhood, associated either with nonmalignant conditions or with subcutaneous panniculitis-like T-cell lymphoma (SPTCL), and often also associated with macrophage activation syndrome (MAS). Discriminating between these 2 conditions is therapeutically important because nonmalignant CHP often improves under cyclosporine and prednisone, whereas most cases of SPLT may be best treated with more aggressive therapy. We report the cases of a 6-month-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…This approach would have a beneficial effect on treatment planning towards oncological rather than anti-inflammatory therapy. Bader-Meunier et al [21] recently emphasized that HLH-associated CHP may be diagnosed despite monoclonal T-cell proliferation that mimics SPTL and is best treated by prednisone and cyclosporine A, at least in children. It has been suggested that this florid clonal T-cell proliferation is reactive, probably driven by a strong immune reaction against EBV infection [22].…”
Section: Discussionmentioning
confidence: 99%
“…This approach would have a beneficial effect on treatment planning towards oncological rather than anti-inflammatory therapy. Bader-Meunier et al [21] recently emphasized that HLH-associated CHP may be diagnosed despite monoclonal T-cell proliferation that mimics SPTL and is best treated by prednisone and cyclosporine A, at least in children. It has been suggested that this florid clonal T-cell proliferation is reactive, probably driven by a strong immune reaction against EBV infection [22].…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the histological findings were different from those of lupus panniculitis: characteristic phagocytic histiocytes (“bean bag” cells) and coagulative necrosis were showed without focal calcifications or cysts bounded by amorphic eosinophilic material. Thus, lupus panniculitis could be excluded [1012]. …”
Section: Discussionmentioning
confidence: 99%
“…[13] The presence of MAS or hemophagocytosis (HPS) might change the management approach and outcome in SPTCL. [14] One study reported 5-year overall survival rates of 91% and 46% in SPTCL patients without and with an HPS, respectively.…”
Section: Discussionmentioning
confidence: 99%